Pengaruh Modifikasi Permainan 4-1 Kucing Bola Terhadap Ketepatan Passing Bagian dalam Pada Kegiatan Ekstrakulikuler Futsal Madrasah Aliyah (MA) di Masa Pandemi Covid-19 - Imam Maulana Hafazhah; Ega Trisna Rahayu; Rizki Aminudin (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to determine whether the modification of the 4-1 cat ball game has an influence on the accuracy of inner passing during the COVID-19 pandemic. This research is included in quantitative research using the experimental method of one group pre-test-posttest design with 10 treatments. The population and sample used were purposive sampling with a total of 14 futsal extracurricular students. The instrument used is the passing accuracy test in Sebagyo Irianto (1995: 9 The t-count value is 11,541, the t-table is 2.16, and the significance value is 0.000 <0.05. It shows that "There is a significant effect in the application of game modifications". 4-1 ball cat on the accuracy of inner passing in extracurricular activities of MAN 1 Bekasi City students". Based on the results obtained from the pretest data, the average score was 6.21, then the posttest had an average score of 8.00. the average difference is 1.79 with a percentage increase of 28.82%..